SEM Analysis of Contractor Performance in Accelerating Electrical Construction Project: Insights from Herzberg's Dual Factor Theory - Saputri, Virda Hersy Lutviana; Nasrulloh (The Industrial Engineering Department of Engineering Faculty at Universitas Andalas, 2024)
In the rapidly developing electrical construction industry, the success of organizations is directly linked to the performance of their business partners. This study focuses on Indonesia's state-owned electrical enterprises, where a notable decline in Key Performance Indicators (KPIs) has raised concerns, hypothesizing that deficiencies in contractor performance are a major barrier to the timely completion of electrical construction projects. At the core of this issue is the role of human resources, identified as a pivotal factor in contractor performance that directly impacts project completion. The aim of the research is to elucidate the complex dynamics between motivator and hygiene factors, which are fundamental to Herzberg's dual factor theory, and their impact on the performance of the contractor's employees. Using Structural Equation Modeling (SEM), the study analyzes data from questionnaires distributed to 250 industry professionals. The analysis provides key insights into how these factors significantly influence job satisfaction and, ultimately, employee performance. These insights play a critical role in strategically planning contractor management practices. By emphasizing the need to understand the key factors driving employee satisfaction and performance, the study lays a solid foundation for designing effective employment contracts and management strategies. The practical implications of this research are significant, offering a pathway for contractors to enhance employee satisfaction and performance. This ultimately leads to the delivery of high-quality electrical infrastructure projects efficiently and promptly, underlining the study's relevance and importance in the contemporary industrial landscape.